'Knowing everything and yet nothing about her': medical students' reflections on their experience of the dissection room. Issue 4 (13th February 2020) - Kassam, Christopher; Duschinsky, Robbie; Brassett, Cecilia; Barclay, Stephen
Abstract : Anatomy education by cadaveric dissection teaches medical students not only the formal curriculum in human anatomy, but also a 'hidden curriculum' whereby they learn the attitudes, identities and behaviours expected of doctors. While dissection has been investigated as a challenge to and training in emotional regulation, little attention has been paid hitherto to the forms of medical knowledge and identity which students encounter and develop in the dissection room. This study analyses a corpus of 119 tributes written by three consecutive cohorts of first-year medical students at a university to their cadaveric donors. We employ a Foucauldian discourse analysis methodology, seeking to elucidate the features of the subject position, the narrative 'I' or 'we' of the tributes, and the modes of knowledge which operate between that subject position and its object, the donor. We observe that students find themselves in a transitional state between personal and scientific modes of knowledge of the human, which correspond to different models of the subject position occupied by the student. While in many tributes these modes exist in an uneasy disjunction, others employ creative reflection to suggest new modes of knowledge and identity which may inform ethical practice.